How to read music [videorecording (DVD)] : keyboard version - Noad, Frederick M.; Noad, Frederick M.; Cooper, Helen (Omnibus Video, 2007)
Frederick Noad teaches the basics of how to read a piece of piano music: pitch, duration, rests and ties, a few familiar tunes, time signatures, sharps and flats, chords and counterpoint, using both hands together, and tempo indications and dynamics.